2019
DOI: 10.1111/2041-210x.13268
|View full text |Cite
|
Sign up to set email alerts
|

An automated approach to identifying search terms for systematic reviews using keyword co‐occurrence networks

Abstract: Systematic review, meta‐analysis and other forms of evidence synthesis are critical to strengthen the evidence base concerning conservation issues and to answer ecological and evolutionary questions. Synthesis lags behind the pace of scientific publishing, however, due to time and resource costs which partial automation of evidence synthesis tasks could reduce. Additionally, current methods of retrieving evidence for synthesis are susceptible to bias towards studies with which researchers are familiar. In fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
152
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(152 citation statements)
references
References 49 publications
0
152
0
Order By: Relevance
“…Instead, the features provided by revtools are likely to be particularly powerful when used in combination with those of related packages. Currently, for example, it is possible to plan a search strategy with litsearchr 35 ; screen your articles with revtools; download articles using fulltext 36 ; analyze the resulting data in metafor 37 or one of the many other meta-analysis packages available in R 9 ; and present a database of study results using EviAtlas 38 . While this is encouraging, many stages of the systematic review workflow remain unsupported within R, with data extraction being a key gap.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the features provided by revtools are likely to be particularly powerful when used in combination with those of related packages. Currently, for example, it is possible to plan a search strategy with litsearchr 35 ; screen your articles with revtools; download articles using fulltext 36 ; analyze the resulting data in metafor 37 or one of the many other meta-analysis packages available in R 9 ; and present a database of study results using EviAtlas 38 . While this is encouraging, many stages of the systematic review workflow remain unsupported within R, with data extraction being a key gap.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the features provided by revtools are likely to be particularly powerful when used in combination with those of related packages. Currently, for example, it is possible to plan a search strategy with litsearchr 35 ; screen your articles with revtools; download articles using fulltext 36 ; analyze the resulting data in metafor 37 or one of the many other meta-analysis packages available in R 9 ; and present a database of study results using EviAtlas 38 . While this is encouraging, many stages of the systematic review workflow remain unsupported within R, with data extraction being a key gap.…”
Section: Discussionmentioning
confidence: 99%
“…We will target grey literature by searching across Google Scholar, DART-Europe E-theses, ProQuest Dissertations & Theses A&I, the Networked Digital Library of Theses and Dissertations Global ETD Search, and OpenThesis. We will use litsearchr [63,64] to search NDLTD Global ETD Search and OpenThesis with the full search string and will use simplified searches (see Table 1) for thesis databases that do not have the capacity to support the full search string. We will not search for grey literature on individual organisational websites, due to resource constraints, but also because relevant literature reviews are highly unlikely to be found here and not elsewhere.…”
Section: Grey Literaturementioning
confidence: 99%
“…Where results cannot be saved as a csv file, they will be downloaded using either Publish or Perish (www. harzi ng.com), the Grey Literature Search Recorder app (https ://www.eshac katho n.org/softw are/grey-lit-repor ter.html), litsearchr [63,64], or custom functions in R to scrape records into a.bib or.ris format where possible. Otherwise, they will be screened in place (i.e.…”
Section: Grey Literaturementioning
confidence: 99%